(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the distinctive and often criticized stylistic features of Theodore Dreiser’s work, particularly Sister Carrie. Critics such as James Phalen, Donald Pizer, and John Flanagan point out Dreiser’s linguistic shortcomings, including vagueness, pretensions, and syntactic errors. Despite these flaws, Dreiser’s raw, unrefined style aims to present an unfiltered depiction of life, characteristic of naturalism. His stories often combine fiction and reality, creating a complex picture of the characters’ dual identities and societal influences. The use of symbolism and irony further emphasizes the themes of deception and social criticism, especially in the portrayal of sibling relationships and gender roles. Dreiser’s deterministic worldview and depiction of random events emphasize the limitations of human choice in his works.